High-Quality Samples for Next-Generation Sequencing and PD-L1 Assessment in Non-Small Cell Lung Cancer: The Role of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration - Marta Rodríguez González; Juan Carlos Montero González; José María Sayagués Manzano; Tamara Clavero Sánchez; Jonnathan Roldán Ruiz; Miguel Iglesias Heras; María Belén Rivas Marcos; Mar Abad Hernández; Rosa Cordovilla Pérez (Diagnostics)
Background/Objectives: Recent advances in the treatment of non-small cell lung cancer (NSCLC) have shifted from conventional chemotherapy to targeted therapies aimed at specific genetic mutations, particularly in the adenocarcinoma subtype. These therapies have improved overall survival and quality of life. However, some patients still face barriers to accessing these treatments due to challenges in diagnosing advanced-stage NSCLC. Limited tumor cellularity in small biopsies and cytological samples hinders the ability to perform further molecular analyses. Additionally, the increasing number of genetic alterations requiring testing complicates the diagnostic process. To overcome this challenge, we propose combining endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) with next-generation sequencing (NGS) and immunohistochemistry for PD-L1. Methods: A total of 120 EBUS-TBNA samples were consecutively collected during the first year of integrating NGS at a reference hospital in Castilla y León, Spain. Depending on the histology and patient characteristics, a total of 67 NGS analyses and 116 PD-L1 determinations were performed. Results: The cytological sample obtained in these cases successfully achieved the triple objective proposed by the NCCN for lung cancer (diagnosis, staging, and molecular analysis in a single procedure) in 97% of instances. Conclusions: Our study highlights the effectiveness of EBUS-TBNA as a comprehensive, cost-effective, and safe diagnostic tool for NSCLC, successfully achieving the triple objective of diagnosis, staging, and molecular analysis in 97% of cases. The procedure consistently provided high-quality samples for NGS and PD-L1 testing, with minimal complications, reinforcing its value as a reliable approach for optimizing personalized treatment strategies.